THE POLYSEMY OF THE ENGLISH VERB OPEN/CLOSE IN “GONE WITH THE WIND” WITH REFERENCE TO VIETNAMESE / Ngô Thị Phương; GVHD: Hoàng Tuyết Minh - Ngô, Thị Phương
The aim of this research is to high light the polysemy of the English verbs open/close in “Gone with the wind” with reference to Vietnamese to help translators use these verbs effectively. The researcher used descriptive method and qualitative to analysis the data There are two semantic features of the verbs open in English from the cognitive semantics perspective. The first is the prototypical of the verb open meaning. It is to separate the edges of something, or to take off its cover so that you can see or remove what is inside. The second is non-prototypical extended meanings of the verb open. It can be said that the most familiar extended meaning of open is “to become available to use, to visit or to see”. There are two semantic features of the verbs close in English from the cognitive semantics perspective.The first is the prototypical meaning of close is as ‘to move to cover an open area’.The second is non-prototypical extended meanings, it means to stop doing business at regular times or temporarily or to stop doing business or operating permanently.